Efek Antidiabetes Kombinasi Infus Biji Oyong (Luffa Acutangula L.Roxb) dengan Metformin dan Glibenklamid - Herowati, Rina; Widodo, Gunawan P; Sulistyani, Putri W; Hapsari, . (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Oyong (Luffa acutangula L.Roxb) seed is a traditional medicinal plant containing flavonoids, saponins, polyphenols and tannins which empirically used to treat diabetes mellitus. Combination of natural product along with conventional drugs has found to be beneficial in certain diseases, such as diabetes mellitus. This research aimed to investigate hypoglycemic effect of combination dose of oyong seed infuse and glibenclamide as well as metformin. Diabetic condition on animal model was conducted by induction of Alloxan as well as by glucose tolerance method. The data obtained were analyzed by one way ANOVA (p<0.05). The result showed that lowering blood glucose effect of oyong seed infusion was higher than that of glibenclamide and metformin on  aloxan induced diabetic mice. Only oyong seed infuse in single administration gave significant lowering effect of blood glucose level on glucose tolerance test.Keywords : Luffa acutangula seeds, alloxan induced diabetic test, glucose tolerance test.